An assessment of proximity technology adoption from a user's perspective - Brohi, Imtiaz Ali; Ali, Najma Imtaiz; Koondhar, Muhammad Yaqoob; Shaikh, I. A; Katper, Naveeda Karim; Shah, Asadullah (University of Sindh, 2018)
The rapid growth and convenience in mobile technologies has attracted every individual in today’s era. Consumer convenience and comfort has remained key focus in almost every industry and such services are also existing and progressing in the domain of other service. Whereas, stakeholders of digital service providers are trying to change the exchange system from one to other society. Whilst, MPs has advanced in some countries, but few are still facing the resistance by people due to dominancy of old system and lack of MP solutions. Whereas, in Pakistan existing MP services are generally offered by FIs and telecom sector. Despite a major share in the market these stakeholders have not played the important role for driving the country towards digital society and bringing the uncovered population of the country into inclusion network. Therefore, this study aims to assess the obstacles in acceptance and use of MPs by using UTAUT model with external variables.